The book of Eli die Zukunft der Welt liegt in seinen Händen - Ross, Atticus 1968- (Universal Pictures, 2010)
Eli walks alone in post-apocalyptic America. He heads west along the Highway of Death on a mission he doesn't fully understand but knows he must complete. In his backpack is the last copy of a book that could become the wellspring of a revived society. Or in the wrong hands, the hammer of a despot. Eli keeps his blade sharp and his survival instincts sharper as his quest thrusts him into a savage wasteland and pits him against a menacing warlord
Bildformat 2.40:1 (anamorph)
Orig.: USA 2009
Enth.außerdem: Lost Tales ; ein Neuanfang ; Elis Reise ; entfernte Szenen ; Die Musik von "The Book of Eli" ; Making-of ; Interviews